IDENTIFIKASI PENYAKIT NON-PATOGEN PADA IKAN NILA (Oreochromis niloticus) BERDASARKAN PARAMETER KUALITAS AIR DI KERAMBA PERAIRAN DESA MALI MALI SEBAGAI INDIKATOR IKAN SEHAT - Mukhlisah; Kisworo, Yulius (Fakultas Pertanian UVAYA Banjarmasin, 2024)
This study aimed to assess the water quality parameters and identify non-pathogenic diseases as indicators of fish health in the Mali-Mali Village Watershed (DAS). The method employed was a survey conducted at the Mali-Mali Village Watershed in Banjar Regency, South Kalimantan. Water quality samples were collected using purposive sampling at observation stations located upstream, midstream, and downstream of the Mali-Mali Village Watershed. The parameters of temperature, pH, and DO were within ranges that supported the cultivation of Nile tilapia in fish cages at the Mali-Mali Village Watershed. However, the parameters of Ammonia and BOD were at levels that did not support the cultivation of Nile tilapia in fish cages at the Mali-Mali Village Watershed. Generally, no clinical symptoms of non-pathogenic diseases were found